Economic Empowerment of Mosques as Provider for Community Economic Services - Rachman Mulyandi, M; Lonica S, Vesya; Yumeina, Tesalonika (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
The number of people in Indonesia is mostly Muslim and has a population of 86.7% in Indonesia. Seeing this, it can be one of the steps to alleviate poverty in Indonesia through the development of economic empowerment where the development of economic empowerment can be carried out through mosques because there are 660 thousand mosques in Indonesia. So the purpose of this study is to analyse the economic empowerment that can be carried out by the Mosque through management or social financial institutions to overcome poverty in Indonesia. Qualitative research method with literature study technique used in this research. The result of this research is that the function of mosques in Indonesia is still used only for worship, so that the funds collected to the mosque manager are only used for mosque operational activities. However, some mosques have implemented economic empowerment development programmes, the concept of which is mostly to provide training to the community so that they are ready to work and provide funding for people who already have businesses. Finally, the importance of the government's role in order to maximise economic empowerment through mosques in Indonesia is needed so that there is a common point of view in managing mosque funds for community economic empowerment. Mosque administrators must also begin to change their point of view regarding the management of funds in the mosque not only for mosque operations, but can also be developed for community economic empowerment.